1992
DOI: 10.1111/j.0033-0124.1992.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Group-Differentiated Perceptions of Social Impacts Related to Tourism Development

Abstract: Perceived social impacts of tourism development on local residents in peripheral destinations are examined in the case of the resort city of Eilat (Israel) by utilizing a value-stretch methodology. Analysis shows that locals' perceptions are group differentiated. The less locals are affiliated with tourist occupations, the less affluent they are, and the less their sense of peripherality, the more they are affected by the social consequences of tourism development.Policy implications for tourism development in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
2
4

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 16 publications
1
58
2
4
Order By: Relevance
“…The factors which influence residents' perceptions and attitudes, as well as the nature and the extent of the impact are likely to be different in each community. Social structure of a local community has a major bearing on its ability to absorb positively the different norms and values brought by tourists (Mansfeld 1992). Nzama (2008) has stated that there is a strong positive relationship between the extent of the community in tourism development and their perceptions towards an increase in tourism development.…”
Section: Community Attitudes To Tourismmentioning
confidence: 99%
“…The factors which influence residents' perceptions and attitudes, as well as the nature and the extent of the impact are likely to be different in each community. Social structure of a local community has a major bearing on its ability to absorb positively the different norms and values brought by tourists (Mansfeld 1992). Nzama (2008) has stated that there is a strong positive relationship between the extent of the community in tourism development and their perceptions towards an increase in tourism development.…”
Section: Community Attitudes To Tourismmentioning
confidence: 99%
“…Although some researchers reported no relationship between length of residence and attitude towards tourism Clements et al, 1993), others have reported a negative relationship. That is, the longer people have lived in the community, the more likely they are to have negative attitudes towards tourism development (Mansfeld, 1992;Stynes and Stewart, 1993;Ryan and Montgomery, 1994;Brunt and Courtney, 1999). Research into other social factors indicates that the state of the local economy (poverty), home ownership and different geographical regions in a country can all influence resident attitudes towards tourism.…”
Section: Attitudes Towards Tourismmentioning
confidence: 99%
“…A society's carrying capacity is considered saturated when locals feel that tourists are a nuisance rather than a benefit. When the mark has been overstepped, the tourist space becomes a sphere of conflict [94,98], of combat among the various actors representing the different interest groups, each of which has a different take on the impact of tourism [113] because of their varying interests. Social resistance and confrontation emerges between tourists and residents, tourists and workers, entrepreneurs and workers, neighbours and entrepreneurs and between conventional entrepreneurs and new sharing economy entrepreneurs and their disruptive innovations.…”
Section: Formal Theory: Tourism Sustainability and Social Conflictmentioning
confidence: 99%